2020
DOI: 10.3390/w12123507
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Use of Quantitative PCR (qPCR), Droplet Digital PCR (ddPCR), and Recombinase Polymerase Amplification (RPA) in the Detection of Shiga Toxin-Producing E. coli (STEC) in Environmental Samples

Abstract: E. coli O157:H7 is a foodborne pathogen that constitutes a global threat to human health. However, the quantification of this pathogen in food and environmental samples may be problematic at the low cell numbers commonly encountered in environmental samples. In this study, we used recombinase polymerase amplification (RPA) for the detection of E. coli O157:H7, real-time quantitative PCR (qPCR) for quantification, and droplet digital PCR (ddPCR) for absolute and accurate quantification of E. coli O157:H7 from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The RPA-based assay has been reported for the detection of E. coli O157:H7 in food samples, using sets of primers targeting specific genes such as rfbE, stx1, stx2, eae, uidA, and fliC [ 29 , 34 , 35 , 50 , 51 , 52 ]. In this present study, two primer sets were selected from the previously tested primers targeting the rfbE and stx2 genes based on their reported sensitivity and specificity [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The RPA-based assay has been reported for the detection of E. coli O157:H7 in food samples, using sets of primers targeting specific genes such as rfbE, stx1, stx2, eae, uidA, and fliC [ 29 , 34 , 35 , 50 , 51 , 52 ]. In this present study, two primer sets were selected from the previously tested primers targeting the rfbE and stx2 genes based on their reported sensitivity and specificity [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…False‐negative results can occur when investigating environmental samples where matrix components, such as humic acids and metals, inhibit the amplification stage (Girones et al, 2010). The degree to which matrix substances inhibit amplification is unknown; however, droplet digital PCR (ddPCR) has been shown to mitigate their effect through dilution (Ibekwe et al, 2020; Stults et al, 2001).…”
Section: Synthesis Of Current Conventional Methods To Assess Microbia...mentioning
confidence: 99%
“…2 and Supplementary Table ST1 summarize the published comparisons of the analytical performance of dPCR and qPCR for health-related water microbiology. Many earlier studies have reported that dPCR and qPCR measurements harmonize well, and both can be reliably used for monitoring various microorganisms in water (Rothrock et al, 2013;Cao et al, 2015;Cao et al, 2016;Verhaegen et al, 2016;Singh et al, 2017;Ibekwe et al, 2020;Crain et al, 2021). However, qPCR and dPCR methods can have considerable differences in performance characteristics, as the enumeration approaches between these methods are fundamentally different (Table 2).…”
Section: Qpcr and Dpcr Comparisonsmentioning
confidence: 97%